Pleural and pulmonary dissemination patterns from gastric adenocarcinoma among patients with treated primary disease in Latin America - Restrepo, Juliana; Carvajal-Fierro, Carlos Andrés; Facundo, Helena; González, Felipe; Ramírez, Ana María; Beltran, Rafael; Buitrago, Ricardo; Jimenez, Andrés-Felipe; Carreño, José; Oliveros, Ricardo (Frontiers in Surgery, 2022)
Purpose: Latin America is one of the regions with the highest incidence of gastric cancer. Even though, there are not reports about the patterns of pleuro-pulmonary metastases in patients with gastric adenocarcinoma treated with curative intent and the prognosis according to each dissemination pattern. Material and methods: we conducted a retrospective analysis of patients with gastric adenocarcinoma treated with curative intent at the National Cancer Institute (INC) between 2010 and 2017. Demographic variables, variables associated with the primary disease and variables associated with the presence of pleuro-pulmonary opacities and metastases were collected. A univariate and multivariate logistic regression analysis was performed and survival curves were presented using the Kaplan Meier method and compared using the log-rank test. A Cox regression model was performed for multivariate analysis for overall survival. Results: the study included 450 patients, 51.3% were male and the median age was 63 years. Intestinal adenocarcinoma was the most frequent histological subtype, in 261 cases (58.0%). Gastric cancer initial pathological stage was stage I in 23.3% of the patients, stage II in 19.3% and stage III in 53.6%. During a median follow-up of 31.9 months, 37(8.2%) patients developed pleuro-pulmonary opacities; among those, 14(3.1%) met the criteria for pleuro-pulmonary metastases: 6(1.3%) had lymphangitic metastasis, 4(0.9%) had a mixed pattern of pleural and lung nodules, 3(0.7%) had pleural metastasis, and only one (0.2%) had hematogenous metastasis. The median OS was 114.5 months for the entire cohort and 38.2 (95%CI,19.2–57.2) months for patients with pleuro-pulmonary metastases. Patients with pleural metastasis and lymphangitic carcinomatosis had median survival of 24.3 (95%CI,0.01–51.0) and 26.4 (95%CI,18.2–34.7) months, respectively. Conclusions: incidence of pleuro-pulmonary metastases in patients with gastric adenocarcinoma treated with curative intention was low. In our series, lymphangitic carcinomatosis was the main pattern of dissemination; meanwhile, hematogenous metastasis was rare and patients with pleural carcinomatosis had the lowest median survival.